PEDAGOGICAL DESIGN AS A MEANS OF INCREASING STUDENTS’ MOTIVATION IN THE E-LEARNING PROCESS - Nakhod Svitlana Anatoliivna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article considers the problem of using pedagogical design as a means of increasing students’ motivation in the e-learning process. It is established that e-learning allows to meet the individual needs of each person in learning and solve such problems of traditional education as lack of individual approach to students, insufficient use of active forms of learning, direct educational process, weak motivation for independent cognitive activity of students, rigid attachment to territory and time, subjectivity of assessment of learning outcomes. Thanks to e-learning, the attendance of events increases due to online participants and records reviewing; new participants and those who cannot be present due to lack of time or geographical distance are involved; access to electronic materials and videos after the lecture is provided; accessibility and cost-effectiveness of education for all categories of citizens is ensured, including the socially disadvantaged and the less mobile is guaranteed; the possibility of choosing individual content and pace of learning is activated; the student’s independent cognitive activity is stimulated. The concept of “рedagogical design” is given as a holistic approach to the organization of educational and cognitive activities of students based on the construction of the educational process as a single system, focusing on learning objectives, didactic material, information and tools available for knowledge transfer in an open information and educational environment. The following principles of pedagogical design are clarified: effective goal setting, scientificity, clarity, accessibility, individualization and differentiation of learning, openness and nonlinearity of the learning process, creation of conditions for constructing one’s own experience, complex influence on all representative systems, reflexivity and feedback, aestheticization of educational environment. The comparative analysis of means of increase of motivation in the course of traditional and e-learning training is implemented, the differences which are reflected in the process of motivation of students are found, such as absence of direct emotional contact of the teacher with students; mechanistic projection of the real world into the virtual one and vice versa; depersonalization of the subjects of the educational process; the difficulty of understanding the educational material. The classical model of increasing students’ motivation in the process of e-learning, ARCS, is considered. The relationship between the stages of pedagogical design according to the ADDIE model and the components of J. Keller’s motivational model ARCS is established. It is concluded that pedagogical design is a means to ensure the active involvement of students in the educational process through the selection and use of a set of interactive forms, methods, techniques and modern information tools by higher education teachers that will ensure the planned result, providing feedback, communication and choice of control and evaluation system in a dialogue mode and optimally taking into account the life experience and future professional development of students. It is emphasized that, taking into account the motivational component, the use of a set of interactive forms and methods, information teaching aids and creative skills of the teacher can ensure effective memorization of the content, reducing time and optimizing effectiveness.